Analisis Dampak Dakwah Gus Iqdam terhadap Dinamika Sosial dan Keagamaan: Studi Kasus pada Masyarakat Karanggayam Blitar - Irma Mufrida; Clara Sinta Pratiwi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the impact of preaching carried out by Gus Iqdam on the social and religious dynamics of the Karanggayam Blitar community. The presence of Gus Iqdam's preaching not only brings influence in the religious realm, but also creates new dynamics in the social realm of society. This study aims to determine the form of preaching carried out by Gus Iqdam, to determine the impact of Gus Iqdam's preaching on the social and religious life of the Karanggayam community, and to determine the factors that influence the level of acceptance and change in society towards Gus Iqdam's preaching. The method used in this study uses a qualitative approach with a case study type. The data collection technique is through in-depth interviews, observation, and documentation. The data obtained are analyzed using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the form of Gus Iqdam's preaching in Karanggayam includes communicative delivery, preaching through personal examples, and empowerment of local congregations. This preaching has an impact on increasing religious awareness in society, forming a more religious environment, and encouraging more positive changes in social behavior. The factors that influence public acceptance of Gus Iqdam include public interest in Gus Iqdam's preaching, emotional closeness between Gus Iqdam and the community, the level of public acceptance of preaching, and Gus Iqdam's personality which is simple and easily accepted by the Karanggayam community.